Vers un modèle d’interprétation et de désambiguïsation sémantique des adjectifs dans des groupes nominaux (appliqué à la traduction automatique franco-polonais) - Thomas, Izabella (Neophilologica, 2004)
This article lays down the basis of an automatic system of interpretation and disambiguation of adjectives (in those noun groups made up of a noun and an adjective), in order to create a machine translation system from French into Polish. It concerns in particular the semantics of adjectives according to their relation with the nouns they describe. Our intention is in fact to describe and predict the semantic compatibility between a noun and an adjective, and more exactly, to formulate the conditions which allow a correct interpretation of the meaning of an adjective in a noun group. This approach results in an algorithm for the semantic interpretation of the meaning of an adjective in a noun group, and, with regards to the machine translation system, in the construction of a language-independent relational intermediary representation.